Relationship between Evapotranspiration and water Availability in the Tropical Regions: A Case Study of a South Western City in Nigeria - T. O. Ogunbode; I. P. Ifabiyi (Archives of Current Research International, 2019)
The understanding of the impacts of evapotranspiration on water supply in time and space is critical to a purposeful water management effort. A study was conducted to examine annual water balance situation in the humid tropical city of Ogbomoso, Oyo State, Nigeria. A thirty-year rainfall and temperature data (1977-2006) were collected from NIMET Office for this purpose. Annual evapotranspiration values were empirically determined using temperature data and Thornthwaite’s model. The study revealed that the major determinant of water balance is the availability of water at the surface which is majorly supplied by green surface and rainfall. Evapotranspiration rate was found to be relatively constant and high above 1000 mm annually ranging from 1249.7 mm in 1980 to 1112.87 mm in 2004 while annual rainfall total varies over the study period of 30 years ranging from 697.1 mm in 2002 to 1595.5 mm in 1998. Results showed that effort should be directed towards urban reforestation and or aforestation, planting of shade trees and other related measures that will encourage water availability for evapotranspiration process for improvement on water balance in the study area.